Cosmopolitan habitat. Urban narratives. Urban design studio. - (:unkn) unknown (My University, 2020)
Starting point for this book is the concept of „Cosmopolitan Habitat“ to inspire thinking, design, and transformation for an open and multidimensional city. Cosmopolitan (from the classic Greek kosmos: world and polis: city) Habitat (from Latin: living space) brings together international debates based on exchange among cultures and communities, places of civilisatory experience, processes supporting a culture of makers and migration. As part of a research in cooperation with the University of Palermo, funded as University Dialogue by DAAD, the Chair for Territorial Design and Urban Planning of Leibniz University Hannover sets the research and design project URBAN NARRATIVES as contribution to an ongoing international investigation and debate on new concepts and tools in urbanism. The central methodological approach is on narratives as analytical and as projectual tools. With the focus on the cities of Halle, Hannover and Flensburg, the book explores how can elements, energies, and networks of a collaborative city overcome spatial and social fragmentation? What role can boundaries, limits, borders, thresholds, and peripheries play for envisioning a “Cosmopolitan Habitat”?
Keywords: Stadtplanung; Stadtgestaltung; Stadtdesign; Stadtumbau; Städtebau; Städtebaulicher Entwurf; Entwurfsseminar; Forschungsprojekt; Stadtentwicklungsforschung; Corona-Krise